The impact of the use of Enjoyable learning strategies in teaching mathematics on the development of the desire produced from the athletic prowess of first-grade students in Makkah ALmukarramah - Al-Afifi, Sawsan Ahmed (Journal of Curriculum and Teaching Methodology, 2022)
The research aimed to identify the effect of using enjoyable learning strategies in teaching mathematics on the development of productive desire among female students of the first intermediate grade in Makkah ALmukarramah, represented in the teacher's guide, the student's guide, and a presentation using the program Microsoft PowerPoint To present it to the students of the experimental group, in line with the transformation of learning to electronic after the Corona pandemic, and a random sample of (68) students was selected, they were divided into two groups, experimental and control, then the tool was applied pre-to-verify the equivalence of the two groups, after that it was applied dimensionally, and then Carrying out statistical treatments using the Statistical Package for Social Sciences; To test the validity of the hypotheses, and the results of the research showed that the interesting learning strategies had an impact on improving the productive desire of the students, and a number of recommendations were reached, including: holding courses and workshops for teachers on how to activate the concept of enjoyable learning while teaching.
Keywords: Enjoyable Learning Strategies; Productive Desire